A incidência de neoplasias associadas à infecção por HPV e a vacinação como uma das estratégias de prevenção primária - Nascimento, Paulo Pereira do (2022)
Objective: Investigate the occurrence of malignant neoplasms associated with HPV infection in a historical series on brazilian regions and the progress of the vaccination against HPV carried out in Brazil. Methodology: This study is based on ecological data within a secondary source, having been based on five Brazilian regions: North, Northeast, Midwest, Southeast and South. The study period was from 2014 to 2020. As aggregate measures were the possibility of malignant neoplasms of the cervix, oropharynx, anus, vagina, vulva and penis; access to protection against HPV; vaccine coverage and vaccine dropout by Brazilian regions. Results: The Brazilian regions, throughout the series, with regard to vaccine coverage goals in their history against HPV, in great totality, did not fulfill an established goal of immunization of 80% of the population, presenting a high rate of defection index of the population and a low access to the vaccine. Regarding the rates of malignant neoplasms of the uterine, cervix, oropharynx, anus, vagina, vulva and penis, is observed the increase of these rates over the years. Conclusion: the incidence of neoplasms has been increasing over the years, and the rates of HPV vaccination coverage has been low, the desertion to vaccination has shown high rates and low access to vaccination.